Serogroup Distribution of Leptospira Among Humans and Rodents in Zakarpattia Oblast, Ukraine (2018–2023) - Pavlo Petakh; Oleksandr Kamyshnyi (Microorganisms)
Leptospirosis is a zoonotic disease caused by Leptospira bacteria, which affects both humans and animals. This study investigated the prevalence of Leptospira serogroups in human and rodent reservoirs across Zakarpattia Oblast, Ukraine, from 2018 to 2023. The objective was to identify epidemiological patterns and assess potential public health risks. Data were sourced from the Public Health Center of Ukraine and regional surveillance initiatives, encompassing reported human cases and rodent-carrier detection. Six main serogroups—Icterohaemorrhagiae, Pomona, Grippotyphosa, Hebdomadis, Canicola, and Tarassovi—were included in the analysis. The results showed that Pomona and Hebdomadis serogroups became more common in 2023. The data from different districts also showed regional differences, with Icterohaemorrhagiae and Pomona being the most frequent serogroups in both humans and rodents. Other serogroups, like Grippotyphosa and Canicola, were found less often. Rodents may be an important source of leptospirosis in Zakarpattia. The growing number of cases in recent years shows the need for improved monitoring, control, and prevention in the region.